In vivo efficacy of tobramycin-loaded synthetic calcium phosphate beads in a rabbit model of staphylococcal osteomyelitis - Godday Anebow Lulu; Arunkumar Karunanidhi; Loqman Mohamad Yusof; Yusuf Abba; Fazlin Mohd Fauzi; Fauziah Othman (BMC, 2018)
Abstract Background Osteomyelitis is an acute or chronic inflammatory process of the bone following infection with pyogenic organisms like Staphylococcus aureus. Tobramycin (TOB) is a promising aminoglycoside antibiotic used to treat various bacterial infections, including S. aureus. The aim of this study was to investigate the efficacy of tobramycin-loaded calcium phosphate beads (CPB) in a rabbit osteomyelitis model. Methods Tobramycin (30 mg/mL) was incorporated into CPB by dipping method and the efficacy of TOB-loaded CPB was studied in a rabbit osteomyelitis model. For juxtaposition, CPB with and without TOB were prepared. Twenty-five New Zealand white rabbits were grouped (n = 5) as sham (group 1), TOB-loaded CPB without S. aureus (group 2), S. aureus only (group 3), S. aureus + CPB (group 4), and S. aureus + TOB-loaded CPB (group 5). Groups infected with S. aureus followed by CPB implantation were immediately subjected to surgery at the mid-shaft of the tibia. After 28 days post-surgery, all rabbits were euthanized and the presence or absence of chronic osteomyelitis and the extent of architectural destruction of the bone were assessed by radiology, bacteriology and histological studies. Results Tobramycin-loaded CPB group potentially inhibited the growth of S. aureus causing 3.2 to 3.4 log10 reductions in CFU/g of bone tissue compared to the controls. Untreated groups infected with S. aureus showed signs of chronic osteomyelitis with abundant bacterial growth and alterations in bone architecture. The sham group and TOB-loaded CPB group showed no evidence of bacterial growth. Conclusions TOB-incorporated into CPB for local bone administration was proven to be more successful in increasing the efficacy of TOB in this rabbit osteomyelitis model and hence could represent a good alternative to other formulations used in the treatment of osteomyelitis.